2014 IEEE International Conference on Pervasive Computing and Communication Workshops (PERCOM WORKSHOPS) 2014
DOI: 10.1109/percomw.2014.6815236
|View full text |Cite
|
Sign up to set email alerts
|

Can we reduce waste and waist together through EUPHORIA?

Abstract: Abstract-Food waste has received little attention in pervasive computing. In this paper we discuss previous work which stresses the need for understanding how intelligent technology could prevent food waste in households. We present EUPHORIA, a community based social system that can track users' food waste potential and redirect behavior, through social influence strategies, towards more sustainable food related practices. To promote social interaction, the system recommends social recipes based on available f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We could nonetheless point out a few community-based social networks that apply pervasive computing to address this challenge, such as EUPHORIA (standing for Efficient food Use and food waste Prevention in Households through Increased Awareness) [11], which is a project that allows users to log and track their everyday food related behavior and redirect these, through social influence, towards more sustainable food related practices. Nonetheless, the project has focused on social behavior around food consumption (necessitating manual inputs via a mobile application), and has not proposed any IoT-based services to automate the discovery of food in the neighborhood that is e.g.…”
Section: Related Workmentioning
confidence: 99%
“…We could nonetheless point out a few community-based social networks that apply pervasive computing to address this challenge, such as EUPHORIA (standing for Efficient food Use and food waste Prevention in Households through Increased Awareness) [11], which is a project that allows users to log and track their everyday food related behavior and redirect these, through social influence, towards more sustainable food related practices. Nonetheless, the project has focused on social behavior around food consumption (necessitating manual inputs via a mobile application), and has not proposed any IoT-based services to automate the discovery of food in the neighborhood that is e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Systems designed for action was argued to have impacts on creativity, pleasure and nostalgia, gifting, connectedness and trend-seeking behaviors [16]. Encouraging collective action is a major characteristic of Euphoria [10].…”
Section: Related Workmentioning
confidence: 99%
“…Social mechanisms that humans use to influence others, such as social approval, peer pressure, norm activation or social comparison, are principles that can be applied successfully for supporting behavior change [18]. The use of social influence strategies is another major characteristic of Euphoria [10]. Studies have shown that our social environments are important determinants of food waste related behavior [5][6], stemming from cultural practices, signaling social status, but also emerging behavior in an age of abundant choice and quantity of food.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the impacts of food loss and food waste on food security and environment have become a global concern as the population grows fast and food production resources become even more limited (Lim et al, 2014). Food is lost or wasted throughout the supply chain -from farm to fork.…”
Section: Food Waste and Its Impactsmentioning
confidence: 99%